Analisis Petugas Aviation Security Dalam Penerapan Standard Operating Procedure Pada Security Check Point (SCP) Di Bandar Udara Sultan Babullah Ternate - Salsabila Oktaviani Ramli; Teguh Ariebowo (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
Safety in the aviation world is the responsibility of the Avsec unit which is in charge of checking passengers and passenger luggage. Negligence of Avsec officers in carrying out their duties can endanger flights. There was a dangerous action that occurred at Sultan Babullah Ternate Airport, where the X-RAY machine at SCP1 at the airport was found to be unattended by officers properly on August 12, 2022.This causes all passengers' luggage to be completely unchecked. This study aims to determine the supervision carried out by the Aviation Security unit in maintaining flight security and safety by applying Standard Operating Procedures (SOP) at the Security Check Point (SCP) at Sultan Babullah Ternate Airport and the obstacles it faces. This research is qualitative with primary and secondary data. Primary data are obtained from interviews and observations, while secondary data are obtained from documentation. This research was carried out at the Aviation Security unit at Sultan Babullah Airport Ternate and carried out in April 2023. The result of this study is that surveillance on SCP 1 is carried out by supervising passengers and their luggage where the passengers will go to the limited security area or check-in area. This supervision is carried out because the luggage that will be put on the plane is one of the main factors related to flight safety. Supervision must be carried out optimally because there are passengers carrying dangerous goods, these passengers must be directed to a special inspection room to be checked in detail while the obstacles in the application of Standard Operating Procedures at the Security Check Point (SCP) at Sultan Babullah Ternate Airport, namely there are still many passengers with high positions and high social status arbitrarily against flight rules or inspection rules. In addition, another obstacle is that there are officers who are negligent in carrying out the Standard Operating Procedure at the Security Check Point (SCP) at Sultan Babullah Ternate Airport.